Elderly women’s life styles and levels of physical activity: a pilot study - Catela, David (2018)
The International Physical Activity Questionnaire (IPAQ) is a standardized measure to estimate habitual practice of physical activities. Because of the specificity of different elderly’s life styles, and, consequently, modes of physical activity, the purpose of this pilot study was to analyze differences among ten regular gym practitioners (fitness group) (68,60±3,57 years of age) and ten Senior University students without gym practice (informal group) (71,30±5,54 years of age). The results showed that energy expenditure doesn’t depend solely on regular and controlled physical activity at a Fitness center, and that functional motor activity, as daily life active transportation and domestic and garden activities, resulted in similar energy expenditure. It’s suggested that programs combining energy expenditure and daily life motor activities is a good solution for quality of life enhancement, and an alternative to more standardized fitness practices.